2015
DOI: 10.1517/13543776.2016.1102888
|View full text |Cite
|
Sign up to set email alerts
|

Formulations of deoxycholic for therapy: a patent review (2011 – 2014)

Abstract: In recent few years, DOCA and its derivatives have been used mostly as pharmaceutical excipients for solubilizing lipophilic compounds to improve their bioavailability. Other studies have expanded its applications to include enhanced drug permeability and have designed more effective drug carriers by conjugation with polymeric materials. Recently, a synthetic DOCA injection, ATX-101, has shown long-term efficacy in the non-surgical treatment of unwanted submental fat and acceptable tolerability in humans. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…Among them deoxycholic acid (DCA), a naturally occurring bile acid, emulsifies fat for absorption in the intestine with nonselective cell-lysis ability 11 and acts by irreversibly disrupting the adipocyte membrane causing adipocytolysis. 12 DCA injection (ATX-101; KYBELLA [United States], BELKYRA [Canada]; KYTHERA Biopharmaceuticals, Inc., Westlake Village, CA, acquired by Allergan, Inc.) is a proprietary formulation of synthetically derived DCA that is FDA-approved for improvement in the appearance of moderate to severe convexity or fullness associated with submental fat.…”
mentioning
confidence: 99%
“…Among them deoxycholic acid (DCA), a naturally occurring bile acid, emulsifies fat for absorption in the intestine with nonselective cell-lysis ability 11 and acts by irreversibly disrupting the adipocyte membrane causing adipocytolysis. 12 DCA injection (ATX-101; KYBELLA [United States], BELKYRA [Canada]; KYTHERA Biopharmaceuticals, Inc., Westlake Village, CA, acquired by Allergan, Inc.) is a proprietary formulation of synthetically derived DCA that is FDA-approved for improvement in the appearance of moderate to severe convexity or fullness associated with submental fat.…”
mentioning
confidence: 99%
“…Steroids, an important class of polycyclic compounds, are prevalent in nature and well known for their diverse and profound biological activities, as well as the abilities of maintaining normal biological functions in living organisms 9 10 11 . Chemical modifications on steroids have long been pursued to generate structurally novel and/or biologically important molecules, especially the incorporation of heterocycles into the steroid core.…”
mentioning
confidence: 99%
“…Moreover, the NaDC aggressiveness and the sudden destruction of fat cells cause the severe pain in injection site in the early days. The cell culture studies also confirmed that NaDC destroys different types of cells such as fat, fibroblast, endothelial and muscle cells [4]. In physiological conditions, NaDC is inactivated and transmitted to the gastrointestinal tract by binding to proteins, including albumin.…”
Section: Discussionmentioning
confidence: 55%
“…NaDC is a type of bile acids, composed of an amphipathic steroid skeleton, with a hydrophilic alpha side, and hydrophobic beta side [3]. Some researchers have sought to use doxycolic acid and ursodeoxycholic acid, as a therapeutic agent with anti-inflammatory, antiviral, anti-cancer, and immune-stimulating properties [4,5]. Subcutaneous injections of NaDC have also shown to reduce size of human lipoma and treat "buffalo hump" in patients infected with human immunodeficiency virus (HIV) [6,7].…”
Section: Introductionmentioning
confidence: 99%